2020
DOI: 10.1093/jaoacint/qsaa164
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aflatoxin M1 in Liquid Milk, Cheese, and Selected Milk Proteins by Automated Online Immunoaffinity Cleanup with Liquid Chromatography‒Fluorescence Detection

Abstract: Background Aflatoxins are secondary metabolites produced by a number of species of Aspergillus fungi. Aflatoxin M1 (AFM1) is a hydroxylated metabolite of aflatoxin B1 and is found in the milk of cows fed with feed spoilt by Aspergillus species. AFM1 is carcinogenic, especially in the liver and kidneys, and mutagenic, and is also an immunosuppressant in humans. Objective A high-throughput method for the quantitative analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A study demonstrated the use of a high-performance liquid chromatography-mass spectrometry (LC–MS) technique to analyze the aflatoxin concentration in baby food in the range 0.003–0.008 μg/L [ 90 ]. In milk samples, high performance liquid chromatography (HPLC) coupled with mass spectroscopy or fluorescence detection is reported as a reliable technique for estimating aflatoxin concentrations [ 91 ].…”
Section: Quantification/detection Of Aflatoxinmentioning
confidence: 99%
“…A study demonstrated the use of a high-performance liquid chromatography-mass spectrometry (LC–MS) technique to analyze the aflatoxin concentration in baby food in the range 0.003–0.008 μg/L [ 90 ]. In milk samples, high performance liquid chromatography (HPLC) coupled with mass spectroscopy or fluorescence detection is reported as a reliable technique for estimating aflatoxin concentrations [ 91 ].…”
Section: Quantification/detection Of Aflatoxinmentioning
confidence: 99%
“…Meanwhile, Wood et al (2020) developed a sophisticated method for determining AFM 1 in liquid milk, cheese, and other selected milk-based proteins. The technique used automated online immunoaffinity clean-up with HPLC-FLD.…”
Section: Chromatography With Non-ms Detectionmentioning
confidence: 99%
“…In developing this high-throughput approach for the quantitative analysis of AFM 1 , Wood and colleagues extracted AFM 1 in protein products using 1% ethanoic https://www.wageningenacademic.com/doi/pdf/10.3920/WMJ2021.2752 -Sunday, March 06, 2022 7:43:18 PM -IP Address: 44.224.250.200 acid diluted in acetonitrile with citrate salts. The AFM 1 in the resulting extract was subsequently concentrated and purified by utilising RIDA® CREST/IMMUNOPREP® cartridges (R-Biopharm, Pfungstadt, Germany) (Wood et al, 2020). This method was found accurate and precise, with 81-112% recoveries and 4-12% repeatability.…”
Section: Chromatography With Non-ms Detectionmentioning
confidence: 99%
“…There are many detection methods for AFM1. Although instrumental methods, such as gas chromatography and high-performance liquid chromatography [ 8 , 9 ], have the advantages of high sensitivity and strong stability, the complex equipment and tedious sample preparation limit their application in the rapid monitoring of AFM1 in the field [ 10 ].…”
Section: Introductionmentioning
confidence: 99%